The influence of micro influencers and digital marketing on product purchasing decisions at tiktok shop in bengkulu city - Darwin Natalaksana; Meilaty Finthariasari; Andhes Tiani Putri; Ahmad Pitra (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to determine the influence of Micro-Influencers and Digital Marketing on Purchase Decisions of TikTok Shop customers in Bengkulu City, both partially and simultaneously. Using 120 respondents, the research analyzes the impact of these variables through multiple data analysis techniques, including instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results show that Micro-Influencers and Digital Marketing both have a significant impact on purchase decisions individually and collectively, highlighting their crucial role in consumer behavior on TikTok Shop